Hirsutism Caused by Pregnancy Luteoma in a Low-Resource Setting: A Case Report and Literature Review - David Hamisi Mvunta; Fatemazahra Amiji; Mubina Suleiman; Francisco Baraka; Ikrah Abdallah; Mabula Kazabula; Peter J. T. Wangwe; Furaha August (Case Reports in Obstetrics and Gynecology)
Background. Pregnancy luteomas are rare, benign, ovarian neoplasms resulting from increased androgenic activity during pregnancy. Often, they occur asymptomatically and are only diagnosed incidentally during imaging or surgery: cesarean section or postpartum tubal ligation. Most common symptoms associated with pregnancy luteoma include acne, deepening of voice, hirsutism, and clitoromegaly. Most pregnancy luteomas regress spontaneously postpartum. Thus, the management of pregnancy luteomas depends on the clinical situation. Case. We report a case of 28-year-old gravida 2, para 1 who presented at 39+1 weeks of gestation with prolonged labor and delivered by emergency cesarean. Intraoperatively, a huge left ovarian mass was identified and resected, and tissue was sent for histopathology and a diagnosis of pregnancy luteoma was made after the pathological report. Conclusion. The present report emphasizes that pregnancy luteoma is a benign neoplasm and imprudent surgical intervention should be reserved. Proper imaging techniques, preferably MRI or ultrasonography that visualize the size of the ovary and reproductive hormonal profiles, would suffice for the diagnosis and management of pregnancy luteoma.